Morphomolecular identification of two trichodinid coinfections (Ciliophora: Trichodinidae) and their immunological impacts on farmed Nile Tilapia. (13th April 2021) - Attia, Marwa M.; Elgendy, Mamdouh Y.; Prince, Abdelbary; El‐Adawy, Mahmoud M.; Abdelsalam, Mohamed
Abstract: Trichodiniasis is one of the most serious ectoparasitic diseases disturbing tilapia aquaculture worldwide, causing deleterious effects and significant economic losses. This study aimed to characterize two Trichodina species concomitantly infecting farmed Nile tilapia Oreochromis niloticus based on integrated morphological, molecular, and immunological approaches. One hundred and eighty of 250 examined Nile tilapia were found to be infected with trichodinids belonging to the family Trichodinidae, with an overall prevalence rate of 72%. The morphological characterization of trichodinids fixed on Giemsa‐stained smears revealed that fish were concomitantly infected with Trichodina heterodentata and T . centrostrigeata . Subsequently, the phylogenetic analysis of the 18S rRNA gene of the two investigated trichodinids confirmed the detected species' identities. The gene expression levels of MHCIIβ and CD4 gens were increased during the trichodinid infection. Furthermore, potassium permanganate and hydrogen peroxide chemicals, which have well‐known records for treating ectoparasites infections in farmed fish, were successfully verified to control trichodiniasis in a small‐scale trial.